(untitled) (Research, Society and Development, 2020)
This research explained about problematic execution of criminal sanctions for minimum fine in 1945 constitution number 35/2009 concerning on narcotics in legal region of Dharmasraya District Attorney Office and the effort to overcome those problematic based on constitution number 35/2019 concerning in narcotics in legal region of Dharmasraya District Attorney Office. This research used criminal theory and law enforcement theory, the method used here is empirical research category and research location within Dharmasraya District Attorney. The result of this research indicates that the whole problem of criminal concern in narcotics which handled by Dharmasraya District Attorney, none of the convicted people implementing judge decision of criminal sanction. Most of the convicts choose to take a prison sanction as a substitute of paying penalty money rather than paying penalty money itself. There are two main factors of why most convicts choosing that decision, economic limitation of every convicts and the possibility of every convicts to take a prison punishment with a quite short period and it considered better than paying penalty as punishment. On its implementation of making criminal punishment decision, public attorney could not make a maximum effort to make convicts obeying the punishment penalty. Public attorney only able to asking for charge, however if the convicts cannot pay the punishment money, they will get a declaration letter of incapable to pay and being imprisoned.